Groundnut oil treatment for the control of cafforotruchus maeulatus (F) during cowpea storage - Singh, S.R.; Luse, R.A.; Leuschner, K.E.; Nangju, D. (1978)
Groundnut oil at 5 ml/kg completely protected cowpea seeds in storage from Callosobruchus maculatus (F (F.) for up to 180 days. The treatment had no adverse effects on cooking time or taste of the cooked beans or on germination even after 6 months storage. The oil treatment prevented emergence of progeny rather than affecting oviposition or mortality of the adult weevils. Groundnut oil entered the egg of C. maculatus through the micropyle, and in 1 to 2 day old eggs, protoplasmic movement was stopped and the protoplasm coagulated. In 3 to 5 day old eggs, where the larvae were partially or fully formed, larval death occurred within minutes of the entry of the oil.